Food safety management : a practical guide for the food industry - Motarjemi, Yasmine; Lelieveld, Huub (Academic Press, 2014)
This book presents an integrated, practical approach to the management of food safety throughout the production chain.
Title from PDF title page (viewed November 26, 2013).
Keywords: Food industry and trade -- Safety measures.; Food -- Safety measures.; Food contamination -- Prevention.; Food handling.; Food industry and trade.; Food adulteration and inspection.; elektronické knihy; electronic books